1987
DOI: 10.1038/bjc.1987.122
|View full text |Cite
|
Sign up to set email alerts
|

A liver DNA synthesis promoter induced in rat plasma by injection of dimethylnitrosamine (DMNA) or thioacetamide

Abstract: Summary The appearance of a liver DNA synthesis promoter (HP) in rat plasma after dimethylnitrosamine (DMNA) or thioacetamide injection was investigated. After 48 h, DMNA (30mg kg-1 body weight) produced liver (centrilobular) necrosis and intense hepatic regeneration, as assessed by microscopic observations of liver slices, as well as augmented transaminase levels; HP was detectable under these conditions. After 5 days, transaminases and HP returned to normal values (the latter undetectable), coinciding with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…1). TA stimulates DNA synthesis and mitosis in the liver of rats at doses that produce limited necrosis (10,11). The rise in DNA synthesis induced by TA follows a time sequence, which is similar to that seen after partial hepatectomy (12).…”
mentioning
confidence: 64%
“…1). TA stimulates DNA synthesis and mitosis in the liver of rats at doses that produce limited necrosis (10,11). The rise in DNA synthesis induced by TA follows a time sequence, which is similar to that seen after partial hepatectomy (12).…”
mentioning
confidence: 64%
“…Investigations into the mode of action of TA have led to the conclusion that toxicity is dependent on its oxidation in the liver to reactive sulfine metabolites (3). Carnitine, biosynthesized from the essential amino acids lysine and methionine, has been suggested to significantly benefit patients with liver failure (4). L-Carnitine (LC) facilitates entry of long chain fatty acids into mitochondria through acylcarnitine transferase for utilization in energy production (5…”
mentioning
confidence: 99%
“…Accordingly, it was reported that the hepatotoxic effects ofTA are manifested only after metabolic conversion to thioacetamide-S-oxide, which undergoes further oxidative metabolism to an as yet unidentified toxic metabolite (7). TA has been reported to stimulate DNA synthesis and mitosis in the liver of rats at doses that produce limited necrosis (9)(10)(11). The rise in DNA synthesis induced by TA has been shown to follow a time course that is similar to that seen following partial hepatectomy (12).…”
mentioning
confidence: 99%